Numerical Assessment of Dirac Equation System by Means of Homotopy Analysis Method - Panakhov, Etibar S.; Babaoglu, Mine (Amer Inst Physics, 2015)
In this paper, we achieve an approximate solutions of one dimensional Dirac equation system with boundary conditions by using Homotopy Analysis Method (HAM). Comparisons are made between HAM and analytic solution. Solutions two-three dimensional graphs and tables are constructed and necessary comparisons are performed. The convergence of the obtained series solution is discussed plainly. HAM is very powerful and effective. The results reveal that the HAM leads to more accurate results and they indicate that only a few components are sufficient to obtain accurate solutions.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 22-28, 2014 -- Rhodes, GREECE
Keywords: Dirac Equation System; Homotopy Analysis Method